Spillover Effects of Studying with Immigrant Students: A Quantile Regression Approach - Asako Ohinata; Jan C. van Ours (Institute for the Study of Labor (IZA), 2013)
We analyze how the share of immigrant children in the classroom affects the educational attainment of native Dutch children in terms of their language and math performance at the end of primary school. Our paper studies the spill-over effects at different parts of the test score distribution of native Dutch students using a quantile regression approach. We find no evidence of negative spillover effects of the classroom presence of immigrant children at the median of the test score distribution. In addition, there is no indication that these spill-over effects are present at other parts of the distribution.
Keywords: I21; J15; 330; immigrant children; peer effects; educational attainment